Effects of choice white grease or soybean oil on growth performance and carcass characteristics of grow-finish pigs - J M Benz; Michael D Tokach; Jim L Nelssen; Joel M DeRouchey; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2007)
A total of 144 barrows and gilts (PIC) with an initial BW of 97 lb were used to evaluate the effects of dietary fat source and duration of feeding on growth performance and carcass fat quality. Dietary treatments included a corn-soybean meal control diet with no added fat or a 2 × 4 factorial arrangement with 5% choice white grease (CWG) or soybean oil and with-drawal of the fat 0, 14, 28, or 56 days before market (82 days). At the end of each feeding duration, pigs were switched to the control diet. At the end of the study (d 82), jowl fat and backfat samples were collected. Lengthening the duration of feeding soybean oil increased (quadratic, P<0.01) ADG and improved F/G. Increasing the feeding duration of CWG had no effect on ADG, but improved (quadratic, P<0.01) F/G. Increasing the feeding duration of CWG or soybean oil increased (quadratic, P<0.02) dressing percentage with the improvement being greater (P<0.06) for pigs fed CWG compared to pigs fed soybean oil. Gilts had increased (P<0.01) iodine value (IV; more unsaturated fat) compared to barrows. Increasing feeding duration of either soybean oil or CWG increased (quadratic, P<0.01) IV compared to pigs fed the control diet. In summary, adding fat to the diet improved pig growth performance but increased jowl fat and backfat IV. Feeding fat during any stage influenced jowl IV at market with duration of feeding having the greatest response with soybean oil.; Swine Day, 2007, Kansas State University, Manhattan, KS, 2007
Keywords: Kansas Agricultural Experiment Station contribution; no. 08-121-S; Swine day; 2007; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 985; Swine; Fat; Pork quality; Iodine value